2023
DOI: 10.3390/ijerph20021445
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Transparent Parallel-Arranged Micro-Perforated Panels (MPPs) as Sound Absorbers in Classrooms

Abstract: Acoustic deficiencies due to lack of absorption in indoor spaces may sometime render significant buildings unfit for their purpose, especially the ones used as speech auditoria. This study investigates the potential of designing wideband acoustic absorbers composed of parallel-arranged micro-perforated panels (MPPs), known as efficient absorbers that do not need any other fibrous/porous material to have a high absorptive performance. It aims to integrate architectural trends such as transparency and the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The parameter values chosen for this study are based on the previous parametric analysis by the Equivalent Circuit Method [13] and concerned at the same time with manufacturing limitations (applicability). The material was assumed to be rigid so that it does not vibrate and has enough mechanical strength.…”
Section: Production Of the Mppsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameter values chosen for this study are based on the previous parametric analysis by the Equivalent Circuit Method [13] and concerned at the same time with manufacturing limitations (applicability). The material was assumed to be rigid so that it does not vibrate and has enough mechanical strength.…”
Section: Production Of the Mppsmentioning
confidence: 99%
“…To broaden the absorption bandwidth, researchers have explored various structures based on MPP arrangements in series, parallel and combined, which by introducing multiple resonances yield efficient and wideband sound absorption [4][5][6]. Previous works by the authors [7] investigated the potential of transparent parallel arrangement of four MPPs in the impedance tube. Preliminary results have shown that a wider band and higher absorption can be achieved simultaneously by tuning each resonator to an overlapping resonance frequency with the precedent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation